Evaluation of capillary pathologies by nailfold capillaroscopy in patients with psoriasis vulgaris: study protocol for a prospective, controlled exploratory study. Issue 8 (10th August 2018) - Fink, Christine; Kilian, Samuel; Bertlich, Ines; Hoxha, Elti; Bardehle, Felicitas; Enk, Alexander; Haenssle, Holger A
Abstract : Introduction: Psoriasis vulgaris was shown to be an independent factor increasing the risk of several comorbidities such as obesity, diabetes and dyslipidaemia with an increased risk of stroke and myocardial infarction. We hypothesise that early endothelial dysfunction, which plays a crucial role in the pathogenesis of atherosclerosis, may be detected by digital video nailfold capillaroscopy (DVNC) at the level of the dermal capillary microvasculature as a surrogate parameter. Nailfolds represent the only body site allowing for a non-invasive assessment of the capillary microvasculature at a horizontal plane. DVNC is a well-established diagnostic tool for in vivo assessment of the peripheral microcirculation by evaluating the morphology of dermal papillary capillaries. To date, reports on morphological changes of the non-lesional nailfold capillaries in patients with psoriasis vulgaris are scarce and the existing data are not conclusive. Methods and analysis: This is a prospective, single-centre, non-randomised, controlled, exploratory study assessing the capillary patterns in 100 subjects affected by psoriasis vulgaris. Non-lesional nailfold capillaries will be imaged by means of DVNC (Optilia Digital Capillaroscopy System, Optilia Instruments AB, Sollentuna, Sweden) in 50 patients affected by psoriasis vulgaris and 50 healthy controls. Assessments will include a qualitative, descriptive analysis of the nailfold capillaries' morphology, as well as a quantitative investigation (frequency, extent) of changes in capillary patterns. Moreover, patients' characteristics associated with the manifestation of nailfold capillaries' pathologies including well-known cardiovascular risk markers will be studied. Ethics and dissemination: Ethical approval was provided by the ethic committee of the medical faculty of the University of Heidelberg (Ethics approval number S-447/2017). The design and the final results of the study will be published and made available to the public. Trial registration number: DRKS00012856.